An intraplate earthquake that occured near Syowa Station, East Antarctica - Negishi, Hiroaki; Nogi, Yoshifumi; Kaminuma, Katsutada (National Institute of Polar Research, 1998)
P(論文) An intraplate earthquake with m_b 4.6 occurred offshore of the Prince Olav Coast, East Antarctica on September 25, 1996. This earthquake was the biggest and the first one to be located within 500km of Syowa Station (69.0°S, 39.6°E) in the past four decades since seismic observations started under the IGY in 1957. The event was recorded by the broadband seismometers at Syowa Station and Mawson Station (67.6°S, 62.9°E), Antarctica. The moment tensor solution of this event was determined using the waveform inversion technique. The source mechanism indicates north-south compressional strike-slip faulting wih little dip-slip component. A straightforward grid search was applied to the data to evaluate the uniqueness of the solution. The minimum error was obtained for close strike, dip and rake angles that obtained in the inversion, so it can be said that the inversion result is suitable. The earthquake occurred on the gravitational lineament regarded as a fracture zone with NW-SE linear trend. The resultant mechanism has a faulting plane with a strike parallel to the fracture zone. Thus, this earthquake might be a fracturing along the pre-existed lineament inside the Antarctic plate. departmental bulletin paper